Imitation, Mimicry, and the Performance of Americanness in Nabokov’s Pnin - Annika M. Schadewaldt (European Journal of American Studies)
Recent scholarship on Vladimir Nabokov has increasingly drawn connections between his literary works and his scientific interests, first and foremost his thinking on insect mimicry. While this approach to Nabokov’s writing has been productive for several of his novels, mimicry has so far not been considered in relation to Pnin. This article argues that we should understand imitation as one of the novel’s core thematic and aesthetic concerns. Approaching the novel as preoccupied with issues of imitation allows us to see not only how Pnin reframes the immigrant narrative as one of imperfect performance of Americanness but also how it connects the issue of assimilation to larger questions of the aesthetic and ethic education of readers.